Digital Health Interventions for People With Type 2 Diabetes to Develop Self-Care Expertise, Adapt to Identity Changes, and Influence Other's Perception: Qualitative Study - Turnbull, Sophie; Lucas, Patricia J; Hay, Alastair D; Cabral, Christie (JMIR Publications, 2020)
BackgroundA diagnosis of type 2 diabetes (T2D) results in widespread changes to a person's life and can be experienced as an assault on their sense of self. The resources available to an individual influence how the individual adapts to their diabetic identity and subsequently engages in self-care. Digital interventions can be viewed as a resource that people can draw on to adapt to the diagnosis. However, there is an indication that people from disadvantaged groups find digital health technologies more challenging to access and use, which may increase health inequalities. ObjectiveThis study aims to gain insights into how and why people with T2D use digital self-care technology and how experiences vary between individuals and social groups. MethodsA purposive sample of people who had used a digital intervention to help them self-care for their T2D were recruited for the study. Semistructured interviews were conducted, and data were analyzed thematically. ResultsA diverse sample of 21 participants were interviewed. Participants used digital interventions to help them to understand and feel more in control of their bodies. Digital interventions were used by participants to project their chosen identity to others. Participants selected technology that allowed them to confirm and enact their preferred positive identities, both by avoiding stigma and by becoming experts in their disease or treatment. Participants preferred using digital interventions that helped them conceal their diabetes, including by buying discrete blood glucose monitors. Some participants used technology to increase their sense of power in their interaction with clinicians, whereas others used technology to demonstrate their goodness. ConclusionsThe technology that people with T2D have access to shapes the way they are able to understand and control their bodies and support preferred social identities.